2023
DOI: 10.3390/bios13070683
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity of Binary/Ternary Locally Resonant Porous Phononic Crystal Sensors for Sulfuric Acid Detection: A New Class of Fluidic-Based Biosensors

Abstract: This research presented a comprehensive study of a one-dimensional (1D) porous silicon phononic crystal design as a novel fluidic sensor. The proposed sensor is designed to detect sulfuric acid (H2SO4) within a narrow concentration range of 0–15%. Sulfuric acid is a mineral acid extensively utilized in various physical, chemical, and industrial applications. Undoubtedly, its concentration, particularly at lower levels, plays a pivotal role in these applications. Hence, there is an urgent demand for a highly ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…For example, Zaki et al 31 proposed a defective 1D-Pn-BG based on a high-sensitivity fano resonance, but the linearity was missed. Aliqab et al 32 suggested a sensor to detect sulfuric acid concentration using 1D-PnC. Their model recorded a good sensitivity, but the linearity between the peak shift and the acoustic speed was missed.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zaki et al 31 proposed a defective 1D-Pn-BG based on a high-sensitivity fano resonance, but the linearity was missed. Aliqab et al 32 suggested a sensor to detect sulfuric acid concentration using 1D-PnC. Their model recorded a good sensitivity, but the linearity between the peak shift and the acoustic speed was missed.…”
Section: Resultsmentioning
confidence: 99%